Les conséquences juridiques des informations erronées fournies par les préposés de l'Administration publique - Pelletier, Gaston (Les Cahiers de droit, 1982)
Government has, by its administrative hand, permeated practically all fields of human activity. Civil servants are therefore giving about more information than ever, information upon which citizens rely to act in such or such manner. What happens though if the information, given in good faith, happens to be erroneous ? That question is precisely the object of this article. Its author considers and weighs the effectiveness of three recourses ; one whereby the legality of the information would be upheld in spite of its erroneous character ; another whereby, the Government would be held liable for damages sustained by an ill informed citizen ; finally, one for redress in equity before the ombudsman.